HOW TO THINK STRATEGICALLY : Sharpen Your Mind Develop Your Competency, Contribute to Success - Githens, Greg (Palmyra, VA : Maven House, 2019)
A primer for those who want to develop their mental acumen and make strategic impact. Greg Githens' book will help you understand what it means to "be strategic" and how to craft strategy that is effective, powerful, and clever. A competent strategic thinker tolerates ambiguity, notices weak signals, defines the core challenge facing the organization, and designs effective responses with a winning strategic logic.
Includes bibliographical references (pages 261-272) and index.
Keywords: Strategic planning; Success